Islam and postcolonial narrative - Erickson, John (Cambridge University Press, 1998)
John Erickson examines four major authors from the 'third world'--Assia Djebar, Abdelkebir Khatibi, Tahar ben Jelloun, and Salman Rushdie- all of whom have critiqued the relationship between Islam and the West. Erickson analyses the narrative strategies they deploy to explore the encounter between Western and Islamic values and reveals their use of the cultural resources of Islam, and their intertextual exchanges with other 'third-world' writers. These writers, he argues, valorise expansiveness and indeterminacy in order to represent individuals and groups that live in the margins of society.